Miami-Dade Junior College North and South Campuses - Mello, Márcia Maria Lopes de (10º Seminário Docomomo Brasil, Curitiba, 2013, 2013)
The design of the North Campus and South (now Kendall) Campus of the Miami-Dade Junior College (now Miami-Dade College) offer a study in Brutalism as both an appreciation of an ethical socially progressive intention, through the campuses’ master plans, and the 'honesty' nature of the style, an aesthetics described by its tectonic characteristic, presented in a tropical modern architecture context. The open-door policy of the College attracted a diverse student body, under the idealism's spirit of higheducation for all. The master plans and brutalist architecture of the Miami-Dade Junior College North (1961) and South (1967) campuses, designed by the architecture firm Pancoast, Ferendino, Grafton & Skeels (now Spillis Candela DMJM), are a response to a hope of a democratic approach to education. Brutalism as an architecture philosophy was often also associated with a socialist utopian. Architect Hilario Candela, who led the design of the campuses, was highly influenced by transitional spaces during his youth in Cuba. These spaces are what he calls rooms without a roof, the most important spaces in a community. The New Brutalism, defined by Reyner Banham, describes a ‘programme’ or an ‘attitude to architecture’. Hilario Candela wanted to use the campus buildings as well as the in-between spaces, to create a place and then take any and all opportunities to excite the senses. For Hilario Candela, architecture comes with the responsibility of helping to shape the city. In the mind, it's a function of democracy. For this study, the choice of Brutalism as an ethical attitude of an appreciation of socially progressive intention—the uncompromising, anti-bourgeois, posture—is summed with the aesthetics of Brutalism, described by the “honesty”—the sculptural qualities of the architecture. Brutalism, as Kenneth Frampton recalled, was a reform movement that advocated the return to functionalist principles—in services, materials, and structure. Construction, in order to be architecturally effective, must find a convincing tectonic expression. The campuses’ projects show an inventive engagement of materials and methods of construction. The structural system is disciplined by geometric modular proportioning, it is cost efficient and is capable of creating humane spaces. Geometry and proportion, which give discipline to the structure, are complemented by the care with which function is housed and the economy and integrity of its construction. Spatial form and function are joined to an efficiency and ingeniousness of construction. The buildings are strongly unified by their geometries masses and the use of exposed concrete and precast paneled walls. Joint design is a constant concern for the performance and the appearance of the buildings. The exposed structure is sandblasted concrete with precast panels, which have light coral rock aggregate faces and accent areas of all white or brown glass mosaic. Although the buildings are solids elements, open space runs into and through them. Generous roof overhangs produce pronounced shades and shadows. Gray precast exteriors are crisply articulated with strengthening flanges that throw varying shadows as sun angles change. The buildings employ the cantilever to weave together the horizontal and the vertical, making spaces between earth and sky. The College campuses’ social spaces are defined by the interplay of light and shadow; concerns of light in architecture—how to use it, mold it, filter it, control its quality, in Florida and the tropics, to animate the forms and spaces.
Keywords: New Brutalism; community college; college campus social spaces